Root fatigue crack propagation characteristics and its effect on mesh stiffness - WANG Zhiyuan; ZHANG Kun; SHAO Guangjun; SHI Lubing; WANG Dongfei; YU Feipeng (Jixie chuandong)
ObjectiveBased on the theory of linear elastic fracture mechanics and dynamic simulations, a model was proposed to simulate the propagation of root fatigue cracks and calculate the mesh stiffness of gears with root cracks. This model was used to study the crack propagation characteristics in the roots of spur cylindrical gears and their impact on mesh stiffness.MethodsFirstly, the initial crack location was determined through the dynamic simulation of gear dynamic meshing process. Then a tooth root fatigue crack propagation model considering real contact conditions was created, and the propagation path was simulated. Finally, the influence of different crack degree on the mesh stiffness was studied based on the crack simulation path.ResultsThe results show that the fracture pattern of root crack is mainly open pattern, the initial crack mainly spreads towards the edge of the wheel, and the later crack evenly spreads towards the root of the tooth. The influence of cracks on the comprehensive deformation and mesh stiffness is greatest in the meshing process of the single tooth. At the same time, when the crack depth is small, the expansion path has little effect on the comprehensive mesh stiffness of the gear, and this effect is gradually obvious with the increase of the crack depth.